Badati Cultural Design as a Learning Model in Increasing Understanding and Awareness of Prospective Taxpayers - Salamor, Lisye; Metekohy, Louisa Marga; Ritiauw, Samuel Patra; Sapulette, Marlen Serly; Nindatu, Agustinus (KnE Social Sciences, 2024)
The role of the community in development is characterized by a high awareness of paying taxes. People in the age range of compulsory education are potential taxpayers. The existence of badati culture, which is believed to have positive values for the people on the island of Ambon, is then designed in the form of a learning model. Through the implementation of the Badati Learning model, it is expected that it will have an impact on the level of tax awareness of 12th-grade high school students in Ambon City. The Badati model developed has a syntax: (1) formulation of activities, (2) formation of groups in representatives, (3) representatives disseminate to small groups, (4) small groups discuss, (5) the results of small group discussions are returned to the large group, (5) representatives disseminate classically by each representative in the gandong cloth. The research and development method, with the stages of preliminary studies on community leaders and youth leaders in Maluku, model trials. Limited test stages were conducted in two schools, broader test stages were conducted in three schools, and model validation was conducted in two schools. The results of the study illustrated that the Badati model is proven to have a good impact in increasing students' understanding of the importance of tax awareness for development with the average N-gain value at each stage of the trial, which is at a moderate level (limited trial N-gain value 0.6, broader trial, 0.7, and 0.7 validation test). Keywords: Badati learning model, tax awareness